2017
DOI: 10.1371/journal.pone.0184833
|View full text |Cite
|
Sign up to set email alerts
|

Risk of acute gastroenteritis associated with human bocavirus infection in children: A systematic review and meta-analysis

Abstract: Human bocaviruses (HBoVs), which were first identified in 2005 and are composed of genotypes 1–4, have been increasingly detected worldwide in pediatric patients with acute gastroenteritis. To investigate if HBoV infection is a risk factor of acute gastroenteritis in children younger than 5 years old, we searched PubMed, Embase (via Ovid), the Chinese Biomedical Literature Database (CBM), and the Cochrane Library for studies assessing the prevalence of HBoVs in individuals from Oct 25, 2005 to Oct 31, 2016. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 23 publications
(19 reference statements)
5
36
0
2
Order By: Relevance
“…Nevertheless, the significance of this virus as a causative agent in human infections remains unknown, due to high prevalence of co-infection with other viruses in symptomatic patients as well as to frequent detection of HBoV in asymptomatic individuals. A recent systematic review suggests that even though HBoVs are often considered bystanders in acute gastroenteritis course, HBoV-2 infection may increase the risk for this disease (5,10,22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the significance of this virus as a causative agent in human infections remains unknown, due to high prevalence of co-infection with other viruses in symptomatic patients as well as to frequent detection of HBoV in asymptomatic individuals. A recent systematic review suggests that even though HBoVs are often considered bystanders in acute gastroenteritis course, HBoV-2 infection may increase the risk for this disease (5,10,22).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported HBoV associated with respiratory and gastrointestinal tract infections as single pathogens, causing severe disease (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…This is a single-stranded DNA virus that has recently been found as a human pathogen. It belongs to the Parvoviridae family, Parvovirinae subfamily, bocaparvovirus genus; four genotypes have been described (HBoV 1 -4) [23,24]. HBoV has been associated with upper and lower respiratory tract infections, sometimes as a single agent or as a co-pathogen with other viruses.…”
Section: Human Bocavirus (Hbov)mentioning
confidence: 99%
“…Human bocavirus (HBoV) has frequently been detected in fecal samples of children with acute gastroenteritis suggesting its important role in the disease . In our previous study, we have described the genetic diversity and genotype associated severity of HBoV in acute gastroenteritis .…”
Section: Introductionmentioning
confidence: 99%
“…Human bocavirus (HBoV) has frequently been detected in fecal samples of children with acute gastroenteritis suggesting its important role in the disease. 1,2 In our previous study, we have described the genetic diversity and genotype associated severity of HBoV in acute gastroenteritis. 3 The present study aims at understanding the epidemiology and changing pattern of HBoV circulation among acute gastroenteritis cases in Pune, Western India, over a study period of 5 years (2007)(2008)(2009)(2010)(2011).…”
Section: Introductionmentioning
confidence: 99%